Kesederhanaaan Menuju Kemajuan: Pelaporan Keuangan dan Strategi Pemasaran UMKM Kelurahan Sumber Rejo - Wahyu Junaedi; Sendy Dwi Haryanto (Kilau Publishing, 2024)
This community service program aims to enhance the performance of MSMEs in Sumber Rejo Village, Balikpapan, by providing training on simple financial statement preparation and digital marketing strategies, reaching 35 MSMEs with the goal of improving their financial management and online marketing skills. The program, conducted through hybrid training sessions (Zoom and offline), included interactive discussions and hands-on practice. Post-training assessments show a significant improvement in participants' understanding and skills, evidenced by the increased use of digital platforms and improved financial record keeping. The program will continue to support these MSMEs through ongoing mentoring, fostering connections with financial institutions, and facilitating easier access to credit. It is hoped that this program will have a positive and lasting impact on the MSMEs in the area, contributing to their growth and the overall economic development of Sumber Rejo Village.